USING FLIPPED LEARNING MODEL IN TEACHING LISTENING COMPREHENSION TO THE STUDENTS IN SMAN 6 MAROS - Riani, Nindi Rika; Jabu, Baso; Talib, Ahmad (Universitas Negeri Makassar, 2023)
New technologies have given students better ways to invest more productive time in class, such as listening classes. This study focuses on the effect of flipped learning on students' listening comprehension. Its objectives are to evaluate students' reactions to the flipped learning paradigm and to examine the effectiveness of flipped learning in enhancing high school students English listening skills. Quantitative research methodologies were used in this experiment. The outcomes demonstrated that the flipped learning methodology at SMA Negeri 6 Maros increased students' English listening abilities. Based on the questionnaire, students have a positive view of learning English with the flipped learning model. They agreed that using the flipped learning model made them more active in class. The results of this study can be very helpful in guiding the teaching of listening comprehension for high school teachers and improving listening comprehension for high school students.